2021
DOI: 10.29303/dtm.v11i1.423
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cross-sectional area of digester on biogas production rate

Abstract: Biogas has become one of the promising alternative fuels. This is triggered by relative ease of production while on the other hand the raw material is cheap and easy to be obtained. In order to get higher biogas production rate, a work has been done with digester cross-sectional area modification.  Under the modification an improvement in biogas yield was obtained. The research also has opened up new outlook to set up a better digester design for maximum biogas production. The experimental results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Therefore, the ratio of raw materials and liquids used is 1:1. This result aligns with previous research that found this ratio to be the best for producing biogas [11].…”
Section: Methodssupporting
confidence: 92%
“…Therefore, the ratio of raw materials and liquids used is 1:1. This result aligns with previous research that found this ratio to be the best for producing biogas [11].…”
Section: Methodssupporting
confidence: 92%
“…The utilization of raw materials from plants, animals, or even waste by applying the latest technology has been studied to obtain alternative fuels. The goal is to obtain a substitute fuel for both spark ignition and compressed ignition engines [1].…”
Section: Introductionmentioning
confidence: 99%